Europe - on air : interwar projects for radio broadcasting - Lommers, Suzanne 1980- (Technology and European history series, 2012)
Radio broadcasting may seem old-fashioned nowadays, but early radio infrastructures and programs in Europe were the real social media of their time. They laid the foundation for how we experience European unification and global interconnectedness today. 'Europe - on Air' takes you on a tour through the early days of broadcasting. Rarely studied sources from international organizations reveal a wide variety of new actors, activities, and debates that jointly shaped broadcasting and society institutions. These stories often remain underexposed in histories of technology, broadcasting, and Europe. Through contemporary sources, 'Europe - on Air' illustrates how people in broadcasting were debating issues ranging from institutionalizing radio to wireless and wired network construction